2022
DOI: 10.3389/fpubh.2022.965808
|View full text |Cite
|
Sign up to set email alerts
|

The hidden financial catastrophe of chronic kidney disease under universal coverage and Thai “Peritoneal Dialysis First Policy”

Abstract: ObjectiveUniversal health coverage can decrease the magnitude of the individual patient's financial burden of chronic kidney disease (CKD), but the residual financial hardship from the patients' perspective has not been well-studied in low and middle-income countries (LMICs). This study aimed to evaluate the residual financial burden in patients with CKD stage 3 to dialysis in the “PD First Policy” under Universal Coverage Scheme (UCS) in Thailand.MethodsThis multicenter nationwide cross-sectional study in Tha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 29 publications
0
3
0
Order By: Relevance
“…We have considered that in the general population, the prevalence of financial need for material, psychological and behavioral domains is around 20-50% for adults aged 18-64 years and around 15-30% for adults aged ≥65 years [39]. Moreover, in previous studies on CKD patients, FT has a prevalence between 30% and 70% [22,[40][41][42][43][44]. Assuming that we are studying a population of subjects with CKD and that the primary endpoint is dichotomous (presence or absence of FT), we calculated an appropriate number of 137 patients when considering the lower limit of prevalence reported in the literature and 47 subjects when considering the upper limit of prevalence in the general and CKD population, respectively, taking into account a type I error of alpha 0.05 and a power of 80%.…”
Section: Participants (Eligibility Criteria)mentioning
confidence: 99%
“…We have considered that in the general population, the prevalence of financial need for material, psychological and behavioral domains is around 20-50% for adults aged 18-64 years and around 15-30% for adults aged ≥65 years [39]. Moreover, in previous studies on CKD patients, FT has a prevalence between 30% and 70% [22,[40][41][42][43][44]. Assuming that we are studying a population of subjects with CKD and that the primary endpoint is dichotomous (presence or absence of FT), we calculated an appropriate number of 137 patients when considering the lower limit of prevalence reported in the literature and 47 subjects when considering the upper limit of prevalence in the general and CKD population, respectively, taking into account a type I error of alpha 0.05 and a power of 80%.…”
Section: Participants (Eligibility Criteria)mentioning
confidence: 99%
“…Despite universal coverage, the residual financial burden remained high in dialysis patients. Of note, the expenditure from out‐of‐pocket HD spending was 2 times greater than those with PD, mainly related to travelling expenses 31 . A recent cost–benefit study applying the concept of willingness to pay on current real‐practice costs found that the ‘PD‐First’ policy is more cost‐effective than the ‘Free‐Choice Dialysis’ policy given the willingness to pay threshold of 4766 USD 32 .…”
Section: Barriers and Constraints Of The Reformed Dialysis Policy And...mentioning
confidence: 99%
“…Of note, the expenditure from out-of-pocket HD spending was 2 times greater than those with PD, mainly related to travelling expenses. 31 A recent cost-benefit study applying the concept of willingness to pay on current real-practice costs found that the 'PD-First' policy is more costeffective than the 'Free-Choice Dialysis' policy given the willingness to pay threshold of 4766 USD. 32 Home-based PD is more costeffective than in-centre HD and should be promoted, especially in low-resource settings.…”
Section: Barriers and Constraints Of The Reformed Dialysis Policy And...mentioning
confidence: 99%